Behavioral Responses to Inheritance and Gift Taxation: Evidence from Germany - Ulrich Glogowsky (Center for Economic Studies and Ifo Institute (CESifo), 2020)
The desirability of inheritance and gift taxes depends on individuals' tax responsiveness. This paper demonstrates how strongly, and in what way, the German inheritance and gift tax influences taxpayer behavior. To that end, it combines administrative data with cross-bracket tax variation: a convex kink in the tax liability precedes a concave kink. Extending the bunching approach to such double-kinked tax schedules, I document that individuals tailor their taxable wealth transfers to the schedules. One type of response dominates for inheritances: testators engage in testament planning. The magnitude of the testament-planning response is comparable to that of inter vivos gifts. However, neither the overall responses of gifts nor those of inheritances heavily interfere with tax revenue collection: the associated short-run net-of-tax elasticities of taxable wealth transfers lie below 0.1.
Keywords: H20; H20; H21; H24; H26; H31; 330; wealth-transfer tax; inheritance tax; gift tax; estate tax; real responses; tax avoidance; tax evasion; behavioral responses; bunching at kinks